Modulations of Foot and Ankle Frontal Kinematics for Breaking and Propulsive Movement Characteristics during Side-Step Cutting with Varying Midsole Thicknesses. (9th May 2018) - Lin, Yi-Jia; Lee, Shih-Chi; Chang, Chao-Chin; Liu, Tsung-Han; Shiang, Tzyy-Yuang; Hsu, Wei-Chun
Abstract : This study is aimed at determining the effects of midsole thickness on movement characteristic during side cutting movement. Fifteen athletes performed side-step cutting while wearing shoes with varying midsole thicknesses. Temporal-spatial and ground reaction force variables as well as foot and ankle frontal kinematics were used to describe breaking and propulsive movement characteristics and modulation strategies. Regardless of midsole thickness, temporal-spatial variables and breaking and propulsive force during side cutting were statistically unchanged. Significantly greater peaks of ankle inversion and plantarflexion with a thicker sole and greater midtarsal pronation with a thinner sole were observed. Current results demonstrated that hypotheses formed solely based on material testing were insufficient to understand the adaptations in human movement because of the redundancy of the neuromusculoskeletal system. Participants were able to maintain temporal-spatial performance during side cutting while wearing shoes with midsoles of varying thicknesses. Increased pronation for a thinner sole might help reduce the force of impact but might be associated with an increased risk of excessive stress on soft tissue. Increased peak of ankle inversion and plantarflexion for a thicker sole may be unfavorable for the stability of ankle joint. Information provided in human movement testing is crucial for understanding factors associated with movement characteristics and injury and should be considered in the future development of shoe design.